Participation Intentions in Crowdfunding for Publishing in Korea - Seo, Yesol; Paek, Jihyun; Kang, Austin (International Journal of Economics and Financial Issues, 2026)
This study investigates the determinants of participation intentions in publishing-based crowdfunding in Korea, utilizing an extended Technology Acceptance Model. The research examines the influence of three factor categories: platform characteristics, individual traits, and social influences. Data were collected via a structured survey of 220 Korean adults and analyzed using confirmatory factor analysis and structural equation modeling. The empirical results show that perceived ease of use and perceived usefulness are powerful direct antecedents of participation intention, functioning as key mediating mechanisms. Regarding platform attributes, security significantly boosts intentions, while information quality and interactivity have limited direct effects. On a personal level, individual innovativeness and compatibility are strong drivers of engagement, whereas material rewards are not significant. Within the social dimension, subjective norms exert a substantial influence, while social image enhancement does not. These findings suggest that ensuring data security and aligning projects with the intrinsic motivations of the target audience are paramount for success. Furthermore, mobilizing social networks is essential for effective campaigns. The study provides actionable insights for publishers and platform operators to optimize engagement in the evolving Korean crowdfunding landscape.